Trends in Religious Practices and Self-Value of Christian Adolescents: Implication for Character Development in Indonesia - Panca Parulian S.; Gery Altobely Seroh; Katjuk Dhwi Waspodo (STT INTI Bandung, 2025)
In the last five years, there has been very little research on the relationship between religious commitment and self-value of Christian youth in Indonesia for character development. In response, we researched Christian adolescents broadly represented across the Gereja Kristen Perjanjian Baru, Christian Religious Education Students in Bandung, and Immanuel Christian School in Pontianak. We had 480 respondents, and the result is that 89% of adolescents have feelings of self-worth. However, when adolescents assessed feelings of failure, pride, and self-satisfaction, the data revealed that 35% of adolescents have feelings of failure, 49% lack pride in themselves, and 35% have feelings of dissatisfaction. Based on the research results, we recommend three areas for further research and practical implementation for character development among adolescents.